2021
DOI: 10.5194/gmd-14-4797-2021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the PALM model system 6.0 in a real urban environment: a case study in Dejvice, Prague, the Czech Republic

Abstract: Abstract. In recent years, the PALM 6.0 modelling system has been rapidly developing its capability to simulate physical processes within urban environments. Some examples in this regard are energy-balance solvers for building and land surfaces, a radiative transfer model to account for multiple reflections and shading, a plant-canopy model to consider the effects of plants on flow (thermo)dynamics, and a chemistry transport model to enable simulation of air quality. This study provides a thorough evaluation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…The PALM model has been widely used to study flows over both idealized (Letzel et al 2008;Park et al 2012;Gronemeier and Sühring 2019;Nazarian et al 2020;Blunn et al 2022) and real urban canopies (Kanda et al 2013;Park et al 2015;Gronemeier et al 2017) and it has been extensively validated (Fröhlich and Matzarakis 2020;Gronemeier et al 2021;Resler et al 2021). Heinze et al (2015) used the PALM model to study secondorder moment budgets in cloud topped boundary layers and found that the PALM model results agree with the results of other LES models except for the TKE dissipation rate.…”
Section: Large-eddy Simulation Modelmentioning
confidence: 94%
“…The PALM model has been widely used to study flows over both idealized (Letzel et al 2008;Park et al 2012;Gronemeier and Sühring 2019;Nazarian et al 2020;Blunn et al 2022) and real urban canopies (Kanda et al 2013;Park et al 2015;Gronemeier et al 2017) and it has been extensively validated (Fröhlich and Matzarakis 2020;Gronemeier et al 2021;Resler et al 2021). Heinze et al (2015) used the PALM model to study secondorder moment budgets in cloud topped boundary layers and found that the PALM model results agree with the results of other LES models except for the TKE dissipation rate.…”
Section: Large-eddy Simulation Modelmentioning
confidence: 94%
“…Several possible approaches for studying the urban climate can be found in the literature: e.g. Mirzaei and Haghighat (2010), Mirzaei (2015), Moonen et al (2012), Arnfield (2003), Rizwan et al (2008), Grimmond (2007), and Barlow (2014). A common approach is the use of stand-alone urban energy balance (UEB) models.…”
Section: Emissions and Chemistrymentioning
confidence: 99%
“…However, the continuous increase in computational resources makes LES models the most promising method to provide sufficiently detailed and accurate information on how the interaction of heat, moisture and momentum exchanges affects the local urban microclimate. Examples of LES models capable of dealing with the urban terrain are PALM-4U (Maronga et al, 2020;Resler et al, 2021) and OpenFoam2. Indeed, PALM-4U has similar goals and many similarities to uDALES.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing computational capabilities, LES has nowadays become one preferred methodology for the simulation of turbulent flow in the ABL. This includes basic boundary layer studies for convective [12,13] and stable [14][15][16] stratification or terrain induced flows [17,18], as well as a wide range of atmospheric applications, e.g., related to wind energy [19][20][21], or pollutant transport and dispersion in urban environments [22,23]. LES simulations for air safety purposes are, in contrast, still rather sparse and often focus on the potential effects of vegetation and buildings on LLT affecting the runway [24][25][26].…”
Section: Introductionmentioning
confidence: 99%